2022
DOI: 10.12973/eu-jer.11.4.2101
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-Student Performance Criteria During Online Classes due to COVID-19: Self-Report by Postgraduate Students in Education

Abstract: <p style="text-align: justify;">During didactic interactions, teachers and students employ competencies and skills that correspond functionally to one another, and several models propose to typify didactic performances in higher education. For this study, we chose the didactic performance interbehavioral model as the substantive theory to identify six pairs of didactic performance criteria through self-evaluations from graduate students. These included: Competency exploration–precurrent learning behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Self-reports derived from this model of didactic performance have achieved stability and construct validity with restricted models of both teacher and student, and of various disciplines, contexts and educational levels [7,29,41]. Likewise, good goodness-of-fit has been found in predictive structural regression models with structural equation modeling.…”
Section: The Conceptual Framework Of This Studymentioning
confidence: 76%
See 4 more Smart Citations
“…Self-reports derived from this model of didactic performance have achieved stability and construct validity with restricted models of both teacher and student, and of various disciplines, contexts and educational levels [7,29,41]. Likewise, good goodness-of-fit has been found in predictive structural regression models with structural equation modeling.…”
Section: The Conceptual Framework Of This Studymentioning
confidence: 76%
“…For example, it has been reported that the effect of the transfer of digital competencies (information acquisition, communication, self-assessment, access to information, the application of digital security and problem solving), depends on the types of interaction with respect to the level or degree of studies and age groups [27]. On the other hand, discrepancies have been reported between the teacher's perception and the university student's perception of teacher performance and teaching quality [28,29], which are similar in the face-to-face context [7]. Additionally, a digital divide between faculty and students, low digital literacy, and inequality of access and connectivity have been reported [17,30].…”
Section: The Virtualization Of Teaching At the Level Of Higher Educat...mentioning
confidence: 99%
See 3 more Smart Citations